2022
DOI: 10.1111/ajt.16790
|View full text |Cite
|
Sign up to set email alerts
|

Salvage living donor liver transplantation versus repeat liver resection for patients with recurrent hepatocellular carcinoma and Child-Pugh class A liver cirrhosis: A propensity score-matched comparison

Abstract: Hepatocellular carcinoma (HCC) accounts for up to 90% of all primary hepatic malignancies and is the fifth most common malignancy and fourth leading cause of cancer-related death worldwide. 1,2 Treatment choices for patients with HCC are affected by the tumor stage, degree of liver dysfunction, and patient comorbidities.Liver transplantation (LT), liver resection (LR), and radiofrequency ablation are common curative treatment options, although LT is considered the best treatment strategy, as it removes the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…358 In contrast, de novo recurrence can be the target of curative re-operation or local treatment. 249,263,[359][360][361][362][363] Typically, recurrence within 2 years after surgery is classified as early recurrence, and recurrence after 2 years is classified as late recurrence. The risk factors for recurrence can be divided into tumor-related factors and underlying liver disease-related factors.…”
Section: Treatment Of Intrahepatic Metastasis After Hepatic Resectionmentioning
confidence: 99%
See 2 more Smart Citations
“…358 In contrast, de novo recurrence can be the target of curative re-operation or local treatment. 249,263,[359][360][361][362][363] Typically, recurrence within 2 years after surgery is classified as early recurrence, and recurrence after 2 years is classified as late recurrence. The risk factors for recurrence can be divided into tumor-related factors and underlying liver disease-related factors.…”
Section: Treatment Of Intrahepatic Metastasis After Hepatic Resectionmentioning
confidence: 99%
“…Salvage LT should be determined by carefully considering the shortage of liver grafts from deceased donors or the problems related to living donors. 359,375 However, the patients who undergo repeated resection are limited in clinical practice, since they have small residual liver parenchyma after resection and are at risk of additional recurrence. 376 For recurrent HCC which is not indicated for repeated hepatic resection, non-surgical local treatments, such as RFA and TACE, can be applied.…”
Section: Treatment Of Intrahepatic Metastasis After Hepatic Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…358 In contrast, de novo recurrence can be the target of curative re-operation or local treatment. 249,263,[359][360][361][362][363] 249,253,[362][363][364][365][366][367][368] The risk factors related to underlying liver disease are high serum HBV DNA levels before and after surgery for chronic hepatitis B 254,[369][370][371] and persistent active inflammation and degree of hepatic fibrosis for chronic hepatitis C; 371,372 these are associated with late recurrence. In a randomized prospective study of repeated hepatic resection and RFA for intrahepatic recurrence, no statistically significant differences were found in the 5-year DFS and OS between the repeated hepatic resection group and the RFA group (36.2% and 43.6% in the repeat hepatic resection group vs. 30.2% and 38.5% in the RFA group, respectively).…”
Section: Treatment Of Intrahepatic Metastasis After Hepatic Resectionmentioning
confidence: 99%
“…In this context, RH is the preferable treatment option in the case of late intrahepatic HCC recurrence, with preserved hepatic function [3]. However, Yoon et al have recently found that SLT is superior to RH even in patients with Child-Pugh class A [14].…”
Section: Repeat Hepatectomy or Salvage Liver Transplant?mentioning
confidence: 99%